A new evaluation system for dynamic muscular strength characteristics using isoviscous loading - Shigetoshi, K.; Isaka, T.; Kawamura, S. (The Engineering of sport 7, Volume 2, 2008)
Measurement of human muscular strength is one of basic requirements in human motion science. In many previous researches, human torque patterns are measured as a function of joint angle position or a function of joint angle velocity, not both of them. However, the human torque characteristics should be represented by joint angle position and joint angle velocity for measurement of dynamic muscular strength characteristics. For this purpose, isokinetic loading Systems have been used so far. In this paper, we point out that isoviscous loading Systems are more effective than isokinetic loading Systems in order to obtain the torque/joint angle velocity/joint angle position data. To realize the isoviscous loading Systems, we utilize a direct drive motor and impedance control. The impedance control generates isoviscosity by reducing inertia effect and elastic effect. The performance of the loading system with isoviscosity is demonstrated through experimental results at first. Next, in the obtained torque/joint angle velocity/joint angle position data, repeatability on the same subject is confirmed and similarity on the shape of the surface in the three dimensional data space (torque/velocity/position) is investigated.